An overview of continuous device-to-device authentication techniques for the internet of things. (25th March 2021) - Badhib, Arwa; Cherif, Asma; Alshehri, Suhair
Internet of things (IoT) has become an integral part of our daily life. However, this technology exposes many security concerns. With the increasing focus on security and privacy, IoT device authentication becomes a crucial requirement to protect devices against any unauthorised access. Although static authentication ensures the legitimacy of the user or device at the beginning of each session, it does not account for session hijacking that could occur after the initial authentication. Continuous authentication is a more robust authentication technique to ensure security throughout the session. Also, it ensures fast authentication for frequent messages sent during the session. In this research, we analyse the security threats in the context of device-to-device communication. We elaborate on the main authentication requirements for IoT. Additionally, we survey major contributions in authentication and compare them based on the predefined requirements. We believe that the findings of this paper provide valuable information to researchers by presenting new directions for future research.